PENGARUH PELAYANAN KEFARMASIAN TERHADAP KEPUASAN PELANGGAN APOTEK DI WILAYAH KAMPUNG TENGAH KECAMATAN KERAMAT JATI, JAKARTA TIMUR TAHUN 2024 - Sari, Dini Permata; Abidin, Zainal (JIFI (Jurnal Ilmiah Farmasi Imelda), 2025)
Service quality is considered a significant strategy tosatisfy the customer and encourage repeated service whichattracts loyal customers. The purpose of this study is to determine the influence of pharmaceutical services on visitor satisfactionin community pharmacies Kampung Tengah, Keramat Jati District, East Jakarta. The method of this research is descriptive research using quantitative techniques through questionnaires conducted as part of a survey. The population of this study is visitors in community pharmacies in Kampung Tengah, Keramat Jati District, East Jakarta in May 2024. Samples taken from the population used purposive sampling. The results of the calculation using the Slovin technique formula are known that the required sample is 189 respondents. The data analysis technique used a univariate analysis and a bivariate analysis. Based on the results of the study, it shows that there is a strong and significant relationship between the assurance provided by the service provider and the level of visitor satisfaction. There is a significant relationship between empathy and visitor satisfaction. Response time and visitor pleasure are significantly correlated. Visitor pleasure and consistency are significantly correlated. Visitor pleasure and tangible facilities are significantly correlated. The conclusion of the study shows that the profile of pharmaceutical services in apotek is quite good, as indicated by the presence of pharmacists every day at the pharmacy and the active role of pharmacists in pharmaceutical services at the apotek.